Cataract Surgery in Patients with Nanophthalmos: Results and Complications. Issue 2 (March 2016) - Lemos, José A.; Rodrigues, Pedro; Resende, Rui A.; Menezes, Carlos; Gonçalves, Rita S.; Coelho, Pedro
Purpose: To evaluate phacoemulsification surgery results and complications in patients with nanophthalmos. Methods: The records of 9 patients with nanophthalmos who had cataract surgery from January 2011 through January 2015 were retrospectively reviewed. Nanophthalmos was diagnosed by the presence of an eye with an axial length (AL) less than 20.5 mm. The records were reviewed for ocular diagnosis, keratometry, anterior chamber depth (ACD), AL, ocular surgeries, visual acuity, and complications. Results: A total of 14 eyes of 9 patients (8 women, 1 man) with a mean age of 72 years (range 48-86) were reviewed. Mean AL was 18.72 mm and mean ACD was 2.30 mm. Mean preoperative spherical equivalent (+8.55 ± 6.44 diopters (D)) was reduced to +0.30 ± 2.17 D at last follow-up visit. Mean best-corrected visual acuity (BCVA) was +0.68 ± 0.55 logarithm of the minimum angle of resolution (logMAR) preoperatively and improved to +0.55 ± 0.73 logMAR at last follow-up visit. Visual acuity remained stable or improved in 11 eyes. Five eyes did not achieve final BCVA ≥+0.3 logMAR. Complications occurred in 3 eyes (21.4%) and included 1 case of posterior capsule rupture, 1 case of severe iritis and rhegmatogenous retinal detachment 2 weeks postoperatively, and 1 other case of iritis. No postoperative uveal effusion was seen. Conclusions: Although phacoemulsification seems to be relatively safe in nanophthalmic eyes, surgeons need to be aware of the challenges of this procedure in these high-risk eyes. Nevertheless, with careful preoperative evaluation and planning, most cases were uncomplicated and resulted in improvement of BCVA.